Letter (copy) : Article from "Il Popolo d'Italia" - Citrine, Walter, 1887-1983
012b-0026-001 Secretary's WMC/FEM/MT/544 17th July, 1939. Senor J.I. de Lizaso, Basque Delegation, 14, Eccleston Square, LONDON, S.W.1. Dear Senor Lizaso, ARTICLE FROM "IL POPOLO D'ITALIA". Thank you for your letter of the 14th July, forwarding me extract from an article by Matio Appelius, which appeared in "Il Popolo d'Italia" on June 20th, 1939, which I was interested to read together with your comments thereon. Yours sincerely, General Secretary 292/946/12b/26